Bicycle Magic - Enid Blyton
A magical selection of short stories including The Wish That Came True, He Bought a Secret and Silly-One and the Jewels. Each tale contains charming and loveable characters and there is always a moral to the story! Children will fall in love with Enid Blyton's comforting creations, illustrated with detailed black and white line drawings.